Ethernet, Fast Ethernet, Token Ring Technologies - Jurayeva, Mohira; Umarov, Bekzod Azizovich (TLEP – International Journal of Multidiscipline, 2025)
This scientific article analyzes the operating principles, technical characteristics, and importance of Ethernet, Fast Ethernet, and Token Ring technologies in mobile application network infrastructure. The study compares data transmission speed, reliability, latency, and network efficiency. The results indicate that Ethernet and Fast Ethernet technologies play a crucial role in modern mobile application development, while Token Ring is mainly of historical significance.